Exploring Pedagogical Possibilities of Commercials in English Language Classrooms of Kerala - Najela, K. P.; Thomas, Mary Vineetha (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Video-based teaching learning methodology is not a new concept in language classrooms. With the advancement in Internet and technology platforms like YouTube and social media the accessibility of short video clips, educational documentaries, advertisements or films has become very popular and impulsive among the mob. Despite of language, all age groups watch and share such interesting videos, but short commercials are less used as a teaching tool even it constitutes as a greater resource. Though studies are very few on exploring commercials in Language education, using selective and appropriate linking of commercial video in to the academic lessons, definitely will be a wonderful experience and it can positively affect the language learning. Students have been exposed to advertisements or commercials in their daily living which enable them to think, speak and write when responding to commercials. This paper explores a few possibilities of pedagogical applications of short commercial videos to enhance English language skills, particularly based on the of high school English Language textbook of Kerala. The methodology used for the study is textual analysis of a unit in the IXth Standard English textbook and the content review of short commercials. This paper also tries to unfold positive means of commercials in enhancing language skills with an urge that, Educationists should build the capacities of the spirit of critical review, creativity, entrepreneurial and social leadership among students.